2012
DOI: 10.1103/physreve.86.056703
|View full text |Cite
|
Sign up to set email alerts
|

Unified theory for inhomogeneous thermoelectric generators and coolers including multistage devices

Abstract: A novel generalized Lagrange multiplier method for functional optimization with inclusion of subsidiary conditions is presented and applied to the optimization of material distributions in thermoelectric converters. Multistaged devices are considered within the same formalism by inclusion of position-dependent electric current in the legs leading to a modified thermoelectric equation. Previous analytical solutions for maximized efficiencies for generators and coolers obtained by Sherman [J. Appl. Phys. 31, 1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(62 citation statements)
references
References 14 publications
1
61
0
Order By: Relevance
“…It is found when the first variation of the integral disappears: δF=δ0LLdx=0, where scriptL is the Lagrange function depending on the degrees of freedom of the problem. Contrary to the standard variational formulation, Gerstenmaier and Wachutka have used a generalized Euler–Lagrange formulation with the heat equation as side condition. For further calculations we write Eq.…”
Section: Gerstenmaier/wachutka Approach: Variational Formulation For mentioning
confidence: 99%
See 3 more Smart Citations
“…It is found when the first variation of the integral disappears: δF=δ0LLdx=0, where scriptL is the Lagrange function depending on the degrees of freedom of the problem. Contrary to the standard variational formulation, Gerstenmaier and Wachutka have used a generalized Euler–Lagrange formulation with the heat equation as side condition. For further calculations we write Eq.…”
Section: Gerstenmaier/wachutka Approach: Variational Formulation For mentioning
confidence: 99%
“…Following Ref. , it is also advantageous to rewrite the heat equation in terms of the new variable w(x)=jα(x)/κ(x). …”
Section: Gerstenmaier/wachutka Approach: Variational Formulation For mentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the devices made of functionally graded TE materials (FGTM) with inhomogeneous transport properties was first proposed by Ioffe 13 in 1960 and then be widely studied by many researchers to enhance the device performance. [14][15][16][17][18][19] For example, Bian et al 20 found that an enhancement of (∆T) max can be achieved in FGTM with spatial-dependent Seebeck coefficient.…”
Section: Modelmentioning
confidence: 99%